Edukasi Gizi Seimbang Pada Anak Usia Sekolah Di SD Negeri 29 Banyuanyara - Natsir, Amaliah (Universitas Patria Artha, 2025)
Food intake in children with the right nutritional composition in terms of quantity, type, and frequency will improve nutritional status and thus strengthen the body's immune system, so that the child will be able to ward off infection. If a child has already contracted an infection, recovery will be much more difficult. This community service activity aims to provide an understanding to the school and students about the importance of balanced nutrition for school-age children. The activity was carried out at SD Negeri 29 Banyuanyara, Takalar Regency, involving 11 students as participants. The method used was the lecture method. Before providing nutrition education, a pre-test was conducted regarding students' understanding of balanced nutrition. This was then continued with an explanation of balanced nutrition. After this activity, a post-test was distributed to assess the increase in students' knowledge. The results of the activity showed that out of 11 students, only 4 had sufficient knowledge about balanced nutrition. However, after being given counseling and health education, all students (100%) understood the basic concepts of balanced nutrition. This confirms that the counseling carried out successfully reached all participants as a whole. It would be advisable to conduct follow-up efforts regarding students' implementation of a balanced daily diet to gauge the effectiveness of this program.